Impact of physical indicators on ocular development in preschool children - Liu, Xiangxiang; Fu, Jing; Li, Lei; Liu, Peipei; Sun, Yunyun; Li, Huijian; Li, Yuanbin; Zhu, Bidan; Wang, Shana; Qin, Xi (Frontiers in Medicine, 2024)
Understanding the impact of early childhood physical growth on visual development is crucial, as this period marks a critical phase for foundational physical and ocular maturation. The aim of the current study was to investigate the associations between the anthropometric indicators of height, weight, and body mass index (BMI), as well as visual acuity, refraction, and ocular biometrics, in Chinese preschool children.This cross-sectional study consisted of 1477 Chinese 3-to 6-year-old preschool children from nine kindergartens in Tongzhou District, Beijing. Demographic data, height and weight were measured according to a standard protocol, and BMI was calculated. Refractive error was measured via autorefraction in eyes under cycloplegia. Axial length (AL), anterior chamber depth (ACD), lens thickness, and corneal curvature were measured via an IOL Master. The axial length-corneal radius (AL-CR ratio) was defined as the AL divided by the mean corneal radius of curvature. Multivariate linear regression models were used to explore the cross-sectional associations between physical indicators (height, weight and BMI) and visual acuity and ocular developmental parameters in boys and girls.Compared with the children in the fourth quartile for height for a given age and sex, the visual acuity in the fourth quartile was 0.08 less, the refraction was 0.11 D more negative (1.22 D versus 1.33 D), the axial length was 0.62 mm longer, the anterior chamber depth was 0.18 mm deeper, the lens thickness was 0.13 mm thinner, the corneal radius of curvature was 0.1 mm less, and the AL-CR ratio was higher after adjustments were made for age and weight. The association between BMI and visual acuity was statistically significant in girls but not in boys. Older and more obese children had better visual acuity (p<0.001) after adjustments were made for age.Height and higher BMI remained independently related to VA condition, AL and ACD elongation, and corneal flattening in preschool children after controlling for various covariates.These results provide critical insights into pediatric ocular health and emphasize the importance of early detection and intervention in both physical and ocular health in early childhood development.